Murder in the Supreme Court - Truman, Margaret, 1924-2008. (New York : Fawcett Crest, 1984)
The chief clerk to the chief justice is found murdered. The suspects include the Senior Justice and Chief Justice himself.
Young Adult
Young Adult
Wilson's Fiction
Booklist
Keywords: Murder -- Washington (D.C.) -- Fiction; United States. -- Supreme Court -- Fiction; Homicide -- Washington (D.C.) -- Fiction; United States -- Supreme Court -- Fiction; Mystery fiction